The effect of the applied potentials difference on the phase composition of Co nanowires; Journal of Magnetism and Magnetic Materials; Vol. 517 - Kozlovskiy (Kozlovsky) A. Artem; Golota I. Ignat; Zdorovets M.; Tishkevich D. Daria; Zubar T. Tatiana; Trukhanov A. Alex (2021, 2021)
Title screen